2015
DOI: 10.1590/1807-1929/agriambi.v19n9p835-840
|View full text |Cite
|
Sign up to set email alerts
|

Development of seedlings of watermelon cv. Crimson Sweet irrigated with biosaline water

Abstract: A B S T R A C TThe limited access and the scarcity of good quality water for agriculture are some of the major problems faced in agricultural areas, particularly in arid and semiarid regions. The aim of this study was to evaluate the quality of watermelon seedlings (cv. Crimson Sweet), irrigated with different concentrations of biosaline water of fish culture. The experimental design was completely randomized with five treatments, corresponding to biosaline water at different concentrations (0, 33, 50, 67 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
(16 reference statements)
1
5
0
2
Order By: Relevance
“…Similar to the results in this study, a reduction in osmotic potential of the substrate caused by NaCl solution impaired seed germination and development of seedlings in other cucurbits such as watermelon (TORRES, 2007;SILVA et al, 2015), melon (ARAGÃO et al, 2009;SECCO, 2010), and cucumber (MATIAS et al, 2015). Average germination time (AGT), average germination speed (AGS) and germination speed index (GSI) all indicate the speed of germination of seeds and showed similar results ( Figure 2).…”
Section: Resultssupporting
confidence: 84%
“…Similar to the results in this study, a reduction in osmotic potential of the substrate caused by NaCl solution impaired seed germination and development of seedlings in other cucurbits such as watermelon (TORRES, 2007;SILVA et al, 2015), melon (ARAGÃO et al, 2009;SECCO, 2010), and cucumber (MATIAS et al, 2015). Average germination time (AGT), average germination speed (AGS) and germination speed index (GSI) all indicate the speed of germination of seeds and showed similar results ( Figure 2).…”
Section: Resultssupporting
confidence: 84%
“…Results similar to that found in this study were obtained in Cucurbita moschata seedlings from the use of 30 mg L -1 salicylic acid (Rafique et al, 2011). However, Silva et al (2015) found that fish farming wastewater favored the length of Citrullus lanatus seedlings. This was not observed in the present study for the cv.…”
Section: Resultsmentioning
confidence: 99%
“…Quetzale grown under different electrical conductivy of irrigation water, could verify that the accumulation of mass at 44 days after sowing (DAS) was not affected by salinity between 0.6 and 3.98 dS m -1 . While Silva et al (2017) [23] observed a decreasing for fresh mass accumulation of the shoot when increasing salinity levels in 'Crimson Sweet' watermelon. In this sense, it is noted that the tolerance of the species to the salinity varies according to the cultivar [24] and time of exposure to this condition [23].…”
Section: Resultsmentioning
confidence: 89%